2007
DOI: 10.1016/j.steroids.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Xenoestrogens are potent activators of nongenomic estrogenic responses

Abstract: Studies of the nuclear transcriptional regulatory activities of nonphysiological estrogens have not explained their actions in mediating endocrine disruption in animals and humans at the low concentrations widespread in the environment. However, xenoestrogens have rarely been tested for their ability to participate in the plethora of nongenomic steroid signaling pathways elucidated over the last several years. Here we review what is known about such responses in comparison to our recent evidence that xenoestro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 65 publications
1
77
0
Order By: Relevance
“…Rapid modulation of ERK and AKT signaling in response to BPA has been observed in neurons, immune cells, and during brain development (14,(40)(41)(42). As far as we know, no information is available on the involvement of these BPA-induced rapid responses on cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid modulation of ERK and AKT signaling in response to BPA has been observed in neurons, immune cells, and during brain development (14,(40)(41)(42). As far as we know, no information is available on the involvement of these BPA-induced rapid responses on cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the possible mechanisms of action of BPA, both genomic and non genomic modes of action involving ER-like receptors, as well as receptor-independent mechanisms may participate in mediating the effects (Quesada et al, 2002;Walsh et al, 2005;Ropero et al, 2006;Watson et al, 2007). In mussel immunocytes, BPA was shown to interfere with signaling components whose activation plays a key role in mediating the effect of E 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, estrogens can also act through rapid, 'non genomic' mechanisms of action that may be initiated at either membrane or cytosolic locations and can result in both direct local effects (such as changes in ion fluxes) and regulation of gene transcription secondary to activation of cytosolic kinase cascades (Levin, 2005;Vasudevan and Pfaff, 2007). Recent studies demonstrated that xenoestrogens can rapidly and potently elicit signaling through non genomic pathways culminating in functional endpoints (Walsh et al, 2005;Ropero et al, 2006;Tabb and Blumberg, 2006;Waring and Harris, 2005;Watson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This does not exclude that similar effects can also be induced or modulated by other mechanisms, e.g., through membrane ERs and non-genomic signaling pathways (Watson et al 2007) or through ERb. Although ERa was the predominantly expressed ER subtype in gonads and MDs during early differentiation, small amounts of ERb mRNA were also found.…”
Section: Era-mediated Effects In Quail Embryosmentioning
confidence: 99%